ATTITUDE OF CLINICAL MEDICAL STUDENTS IN FAMILY MEDICINE PRACTICE - Rotpenpian, Passorn; Sukareechai, Somchai (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2024)
Family medicine is one of the courses provided in Thailand’s doctor of medical program. Based on the setting of each institution, learning management system improvements vary and continuously. There were some challenges, particularly the students’ attitude. The aim of this study was to compare attitude of clinical medical students in family medicine practice course. This was a prospective comparative study. In the second semester of the academic year 2022, a questionnaire was administered to fifth-year clinical medical students of Srinakarinwirot University before and after they attended a family medicine practice course. The questionnaire’s content validity was confirmed, with an Index of item objective congruence (IOC) value of between 0.50 and 1.00 and an approval quality. Reliability using Cronbach’s alpha coefficient formula is 0.72. The data were analyzed by descriptive statistical method with frequency, percentage, mean, standard deviation, maximum, minimum and analytic statistical method with Paired simple T-test. 78 respondents (90.69%) answered the questionnaire. The findings demonstrated that following the study period, student attitude scores were significantly increased (p-value 0.002). Each aspect was studied, as it showed that getting a positive attitude in all questions, there was a significant change between the before and after sessions (p-value < 0.05). Changes in negative attitude before and after sessions. But for all questions, there was no statistically significant (p-value>0.05). It demonstrates after studying family medicine practice of the medical students, there were higher self-assessed scores in attitude.